Plot Construction of ‘Red Notice’ Movie - Anugrah Prasetya Dharma Putra, I Gede; Maharani, Sang Ayu Isnu; Savitri, Putu Weddha (Humanis, 2023)
The purpose of this study is to identify the plot structure of the Red Notice movie and the technique used in narrating the plot of the Red Notice movie. Documentation method was applied in collecting the data. The collected data was analysed by using informal method which represents the result of the analysis. The result showed the plot structure of Red Notice movie consists of three phases. They are beginning, middle, ending phases. The beginning consists of introducing characters, setting the place, and potential conflicts. Then, the middle which consists of conflict, complication and climax. Finally, is the ending, in this section the story resolution will be given. The technique that was applied in narrating the story was mixed plot since the story moves forward from the first event to the last event. However, a flashback is performed in the middle story